Politik Hukum Agraria Terhadap Hak Ulayat Masyarakat Hukum Adat Di Indonesia - Yusna Elfrida Br.Tambunan; Sulastri Krisdayanti Sinambela; Isnaniah Isnaniah; Joshua Hery Cristian Gultom (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Ulayat rights are the highest control rights of customary law communities covering all land as well as those included in certain regional environments. Customary law looks at societyas the best place to live together where people view their fellow human beings as common goals. This type of research is a type of library research.which relies on study and study of texts. This is done because of the data sources used is in the form of literature data. Customary rights are rights to land owned by the community customary law before the UUPA was created, which can be converted into land rights. Respect and protection of the legal community and its rights are protected nationally, especially in Article 3 UUPA and Article 18 of the 1945 Constitution were amended. The Position of Land in Customary Law In customary law, land has a very important position. In the development process Currently, it is very important for indigenous peoples to participate in development activities.The public has the right to provide verbal and written input in the preparation processor discussion of draft laws and plans for regional regulations.